2008
DOI: 10.1086/521616
|View full text |Cite
|
Sign up to set email alerts
|

Virial Scaling of Massive Dark Matter Halos: Why Clusters Prefer a High Normalization Cosmology

Abstract: We present a precise estimate of the bulk virial scaling relation of halos formed via hierarchical clustering in an ensemble of simulated cold dark matter cosmologies. The result is insensitive to cosmological parameters, the presence of a trace, dissipationless gas component, and numerical resolution down to a limit of ∼ 1000 particles. The dark matter velocity dispersion scales with total mass as log(σ DM (M, z)) = log(1082.9 ± 4.0 km s −1 ) + (0.3361 ± 0.0026) log(h(z)M 200 /10 15 M ⊙ ), with h(z) the dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
449
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(530 citation statements)
references
References 117 publications
76
449
3
Order By: Relevance
“…Numerical simulations confirmed that the σv-M∆ relation is consistent with the self-similar scaling with mass (Evrard et al 2008;Munari et al 2013;Saro et al 2013). Some differences may arise from the galaxy population used to estimate the velocity dispersion and from the impact of selection using galaxy colour, projected separation from the cluster centre, galaxy luminosity, and spectroscopic redshift (Saro et al 2013).…”
Section: σV-m∆supporting
confidence: 65%
See 1 more Smart Citation
“…Numerical simulations confirmed that the σv-M∆ relation is consistent with the self-similar scaling with mass (Evrard et al 2008;Munari et al 2013;Saro et al 2013). Some differences may arise from the galaxy population used to estimate the velocity dispersion and from the impact of selection using galaxy colour, projected separation from the cluster centre, galaxy luminosity, and spectroscopic redshift (Saro et al 2013).…”
Section: σV-m∆supporting
confidence: 65%
“…This is the approach usually followed in numerical simulations (Evrard et al 2008;Munari et al 2013;Saro et al 2013) to built mass proxies based on the velocity dispersion without assuming dynamical equilibrium and without exploiting the properties of the infall patterns.…”
Section: Discussionmentioning
confidence: 99%
“…These biases are always a result of the velocity dispersion. The virial mass is biased simply because it is directly related to the velocity dispersion (Evrard et al 2008). The caustic mass is biased because the standard "caustic" technique calibrates the escape edge to the velocity dispersion (Diaferio 1999;.…”
Section: Particles Versus Subhalosmentioning
confidence: 99%
“…One of more traditional methods is to apply the virial theorem to the projected phase space distribution of member galaxies (e.g., Zwicky 1937;Yahil & Vidal 1977;Evrard et al 2008), maintaining the assumption that the cluster is in virial equilibrium (and sometimes including the surface term, see The & White 1986). Perhaps the simplest of approaches to measure the mass is to use richness: the number of galaxies associated with the cluster above a certain magnitude limit (e.g., Yee & Ellingson 2003).…”
Section: Introductionmentioning
confidence: 99%